INHIBITION TEST OF CUCUMBER’S WATER (Cucumis Sativus L) ON THE GROWTH STHAPYLOCOCCUS AUREUS BACTERIA WITH DISK CAKRAM METHOD - panji wahlanto; marlina indriastuti; desi karningsih; anna lesmana yusuf; davit nugraha (Jurnal Wiyata Penelitian Sains dan Kesehatan, 2020)
Backgrund : Staphylococous aureus infection can cause serious and life-threatening illness if it enters the bloodstream, for example meningitis, endocarditis, and species. Staphylococcus aureus is a very serious problem because of the increased resistance of these bacteria to various types of antibiotics, due to their  inappropriate use. So we need a natural alternative therapy as an antibiotic using cucumber juice. Objectives : The study aims to determine the inhibition of cucumber juice at various concentrations on the growth of Sthapylococcus Aureus. Methods  : Test method for antibacterial inhibition using concentrations of 40%, 60%,80% and using positive control and negative control. Results :   in general cucumber juice have moderate inhibitory ability on the growth of Staphylococcus aureus bacteria, and the most effective concentration is 80%. Conclusions and suggestions : Systemic infection of Staphylococcus aureus cannot be described with the profile of this study, need another research profile that can explain it.